The Impact of Brand Storytelling and Brand Image on Marketing Performance: A Case Study of Grab Indonesia - Hayati, Michelle Zuhrotul; Firdaus; Jumai; Nur Aini, Farikha (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study explores the influence of brand storytelling and brand image, mediated by purchase decisions, on the marketing performance of PT.Grab Teknologi Indonesia, which at the end of 2023 made its first profit in history and reduced Grab's losses from US 1,74 in 2022 to US 485 million in 2023. Using SEM analysis with data from 96 respondents, results indicate that both brand storytelling and brand image significantly enhance marketing performance, with purchase decisions acting as a critical mediating factor. These findings offer strategic insights for improving marketing performance through enhanced storytelling and brand imaging.